Unsteady Free Convective and Mass Transfer Flow through Porous Medium in Rotating System - Sarkar, D; Mukherjee, S; Mukherjee, S (GANIT: Journal of Bangladesh Mathematical Society, 2011)
An exact solution of unsteady free convective and mass transfer flow through porous medium bounded by a vertical porous plate with an oscillating free stream velocity is obtained. The entire system rotates about an axis normal to the plate. Existence of multiple Ekman boundary layer modified by the presence of free convection and mass transfer is observed near the neighbourhood of plate wall. Key words: Porous medium; rotating system; free convective flow; mass transfer. GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 29 (2009) 107-115 DOI: http://dx.doi.org/10.3329/ganit.v29i0.8520